Effects of KRAS, STK11, KEAP1, and TP53 mutations on the clinical outcomes of immune checkpoint inhibitors among patients with lung adenocarcinoma. - Yao Liang; Osamu Maeda; Chiaki Kondo; Kazuki Nishida; Yuichi Ando (PLoS ONE)
Background This study aimed to identify the associations between individual KRAS, STK11, KEAP1, or TP53 mutations, as well as the comutation status of these genes, and the tumor mutation burden (TMB) with clinical outcomes of lung adenocarcinoma patients treated with immune checkpoint inhibitors (ICIs). Methods We collected data from patients with lung adenocarcinoma treated with ICIs from the Center for Cancer Genomics and Advanced Therapeutics (C-CAT) database between June 2019 and August 2023. The main endpoints were the treatment response and overall survival (OS). Results Among 343 patients with lung adenocarcinoma, 61 (18%), 69 (20%), 41 (12%), and 222 (65%) patients had KRAS, STK11, KEAP1, and TP53 mutations, respectively. An overall objective response was observed in 94 of 338 patients (28%), including 2 (1%) who achieved a complete response and 92 (27%) who achieved a partial response. Patients with STK11, KEAP1, or TP53 mutations had a significantly greater TMB (P<0.001). According to the univariate analysis, the treatment response was significantly correlated with TP53 mutation in both the general (P = 0.041) and KRAS wild-type (P = 0.009) populations. KEAP1 and TP53 mutations were associated with worse OS among assessable patients (hazard ratio (HR) = 2.027, P = 0.002; HR = 1.673, P = 0.007, respectively) and among patients without KRAS mutations (HR = 1.897, P = 0.012; HR = 1.908, P = 0.004, respectively). According to the multivariate analysis, KEAP1 (HR = 1.890, P = 0.008) and TP53 (HR = 1.735, P = 0.011) mutations were found to be independent factors for OS. Conclusions STK11, KEAP1, and TP53 mutations are significantly associated with a high TMB. TP53 mutation could affect the treatment response to some degree, and both KEAP1 and TP53 mutations resulted in inferior OS in the general patient population and in those with KRAS-wild-type lung adenocarcinoma, indicating that KEAP1 and TP53 mutations might act as prognostic factors for ICI treatment in lung adenocarcinoma patients.